2019
DOI: 10.1002/app.47645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pressure on poly(ether‐ether‐ketone) (PEEK) sintering mechanisms

Abstract: This study deals with the understanding of the sintering mechanisms that occur during consolidation of an ultra-highperformance polymer: poly (ether-ether-ketone). In particular, we investigated the effects of uniaxial pressure during spark plasma sintering (SPS) processing. Glass-transition temperature (T g ) measurements under loading, stress-strain curves and scanning electron microscopy analysis allowed us to determine the role of pressure intensity and temperature of application on macromolecular chain mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…These processes, referred to as polymer sintering, have already shown promising results in producing dense and homogeneous polymer parts. [13][14][15][16][17][18][19][20][21] The sintering of polymer powders differs from that of other materials, such as metals or ceramics, due to their viscous nature. 22 Polymers are indeed composed of both free macromolecular chains, that constitute the amorphous region, and of crystalline regions where the macromolecular chains rearrange themselves into crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes, referred to as polymer sintering, have already shown promising results in producing dense and homogeneous polymer parts. [13][14][15][16][17][18][19][20][21] The sintering of polymer powders differs from that of other materials, such as metals or ceramics, due to their viscous nature. 22 Polymers are indeed composed of both free macromolecular chains, that constitute the amorphous region, and of crystalline regions where the macromolecular chains rearrange themselves into crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the potential of SPS technology to consolidate polymers and polymer composites. [13][14][15]17,18,20,[30][31][32][33] For instance, Sébileau et al 14 successfully consolidated homogeneous PEEK samples by SPS. They defined a Design of Experiments to assess the effect of temperature, dwell time and pressure during sintering on the density ρ ð Þ, Young's modulus (E) and Compressive yield strength (σ y ) of PEEK specimens.…”
Section: Introductionmentioning
confidence: 99%
“…In particularly, pressure allows the synthesis of materials, even with different thermal stabilities precursors [ 9 ]: to orientate the chemical reaction in the direction of synthesis leading to the densest phase by the Le Chatelier principle (ex: synthesis of diamond to the detriment of graphite), e.g., [ 10 , 11 ]; to initiate a new finer microstructure by driving the phase transformation in polymorphic materials (ex: Al 2 O 3 : γ → α), e.g., [ 12 , 13 ]; to improve the chemical reactivity for refractory materials sintering (borides, nitrides, carbides) to better densification compared to lower pressure processes, e.g., [ 14 , 15 ]; to allow the sintering beyond the thermal decomposition temperature by the condensation effect, i.e., pressure stabilizing structure (ex: MgB 2 ), e.g., [ 16 ]; to sinter the high-pressure stable phase in the high-pressure stability domain (ex: c-C, c-BN), e.g., [ 17 ]; to adjust the porosity, close to 0% (ex: transparent ceramics) or high porosity ( p > 50% ) (ex: bone structure mimetic), e.g., [ 18 ]; to increase the thermal stability of precursors by condensation effect by avoiding the departure of OH − , H 2 O, others volatile elements) [ 19 ]; to decrease the sintering/consolidation/densification temperature by its driving force in order to avoid grain growth (which is always activated by high temperature), e.g., [ 20 ]; to favor the structural phase existing only at lower temperature (ex for amorphous calcium phosphate), e.g., [ 21 ]; to allow the consolidation of thermally unstable materials such as organic materials (ex: polymer) [ 22 ] and to allow the consolidation of composite constituted by materials of different thermal stability (ex: polymer composites) [ 23 ]. …”
Section: Introductionmentioning
confidence: 99%
“…to allow the consolidation of thermally unstable materials such as organic materials (ex: polymer) [ 22 ] and to allow the consolidation of composite constituted by materials of different thermal stability (ex: polymer composites) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by powder metallurgy, sintering is a well‐established procedure for producing functional polymeric parts such as separation membranes, 1 orthopedic implants, 2,3 bio‐engineered scaffolds, 4 and drug‐release media 5,6 . Also, in cases where conventional melt processing is not feasible, sintering is a viable procedure for producing polymeric parts.…”
Section: Introductionmentioning
confidence: 99%